Analysis of assistance in sexually transmitted infections primary care (Research, Society and Development, 2020)
It aimed to evaluate the assistance in sexually transmitted infections provided in primary health care by nurses and doctors from a gender perspective. This was a cross-sectional study with quantitative approach, conducted with 32 nurses and 32 physicians from Family Health Units between January and June 2016. Data collection was carried out using a form and the data was tabulated and analyzed with Epi infoTM7 software. Results regarding the clinical activities developed identified the prevalence in professional nurses performing gynecological care, physical and clinical examinations of the breasts on female people. In opposition, medical professionals predominated in performing physical and genital examinations on male subjects. Regarding the perceptions of professionals about the influential aspects in the transmission of sexually transmitted infections, the following were highlighted: immunity, promiscuity, machismo, periphery and low schooling. Results demonstrated the presence of aspects that reinforce normative standards influencing assistance in sexually transmitted infections. Moreover, the restrictive view of risk groups, including gender barriers, can make it difficult to carry out prevention activities and approach in user care.